Prevalence of Gastrointestinal Parasites of African Catfish (Clarias gariepinus) from River Nasarawa, Nasarawa State, Nigeria - Aliyu, A.A.; Abubakar, B.S. (Sahel Journal of Life Sciences FUDMA, 2024)
Fish and fish products are significant sources of nutrients for humans. Parasites of fish are of concern since they often produce a weakening of the host’s immunity thereby increasing susceptibility to secondary infections. This study was conducted with aimed to examine the prevalence of gastrointestinal parasites infecting fish. Field study was conducted during the period from September to November 2022. A total of 200 fish samples (Clarias gariepinus) were examined for the presence of gastrointestinal parasites. Result show that, total number of fishes infected 60(30.0%) out of which 26(26.26%) males and 34(33.66) female. Two helminths one each from Cestode and Nematode were isolated from the infected fishes. The Cestode and its prevalence were Diphylobothrium latum (5%) and nematode Procamallanus spp. (3.33%). The protozoa recovered included: Hexamita spp., Protoopalina spp. and Microsporidia with 60.00%, 23.33% and 18.34% respectively. The majority of the parasites were found in the intestine. Fish specimens that were lighter in weight 10 -200g had less infection (12.5%) but those found with parasites weighed between 201-400g (42%). There was no significant difference (P>0.05) in the infection between male and female Clarias gariepinus and with age on the prevalence and intensity of the gastrointestinal parasite. Wild fish (Clarias gariepinus) in River Nasarawa have a high prevalence of intestinal parasites, therefore it is recommended to avoid open defecation that finally is washed down to rivers and streams hence affecting the aquatic organisms and to properly cook wild fish obtained from River Nasarawa before consumption for safety.